Emerging roles of innate lymphoid cells in inflammatory diseases: Clinical implications. Issue 4 (22nd November 2017) - Kortekaas Krohn, I.; Shikhagaie, M. M.; Golebski, K.; Bernink, J. H.; Breynaert, C.; Creyns, B.; Diamant, Z.; Fokkens, W. J.; Gevaert, P.; Hellings, P.; Hendriks, R. W.; Klimek, L.; et al.
Abstract: Innate lymphoid cells (ILC) represent a group of lymphocytes that lack specific antigen receptors and are relatively rare as compared to adaptive lymphocytes. ILCs play important roles in allergic and nonallergic inflammatory diseases due to their location at barrier surfaces within the airways, gut, and skin, and they respond to cytokines produced by activated cells in their local environment. Innate lymphoid cells contribute to the immune response by the release of cytokines and other mediators, forming a link between innate and adaptive immunity. In recent years, these cells have been extensively characterized and their role in animal models of disease has been investigated. Data to translate the relevance of ILCs in human pathology, and the potential role of ILCs in diagnosis, as biomarkers and/or as future treatment targets are also emerging. This review, produced by a task force of the Immunology Section of the European Academy of Allergy and Clinical Immunology (EAACI), encompassing clinicians and researchers, highlights the role of ILCs in human allergic and nonallergic diseases in the airways, gastrointestinal tract, and skin, with a focus on new insights into clinical implications, therapeutic options, and future research opportunities.